Hinduism in five minutes - Ramey, Steven W. (Religion in 5 minutes, 2022)
Preface / Steven Ramey -- General questions -- Beginnings -- Development -- Texts and Stories -- Gods and Goddesses -- Personal practices -- Rituals and Worship -- Hindus in relation to non-Hindus -- Current Issues.